Heat Transfer Analysis of the Flat Plate Solar Thermal Collectors with Elliptical and Circular Serpentine Tubes - Shirin Rostami; Ag Sufiyan Abd Hamid; Kamaruzzaman Sopian; Hasila Jarimi; Anwor Bassim; Adnan Ibrahim (MDPI AG, Basel, Switzerland, 2022)
In this study, the heat transfer characteristics of the flat plate collectors with circular and elliptical serpentine tubes are theoretically analyzed and compared in terms of . m, Re, Nu, hf i, FR, Qu, and µTh under various water flow rates and the standard test conditions. The results reveal that the maximum µTh correspondence to the elliptical serpentine design with 56% under turbulent flow, and the minimum µTh of 47% for the circular cross-section under laminar flow. In addition, it was found that the highest useful energy gain per unit time (493.8 W) through the system is possible when FR, hf i, Nu, and . m are maximum and vice versa. It was concluded that, at the same area, the larger contact area in the elliptical cross-section compared to the circular would improve FR and Qu by an average of 2%. Overall, it is crucial to evaluate the thermal parameters of the thermal collector during the preliminary design stage to fabricate a highly efficient system and save time as well as initial cost.